STABILITAS PARAMETRIK HASIL 14 GENOTIPE TOMAT (Solanum lycopersicum L.) DI EMPAT LINGKUNGAN DATARAN RENDAH - Dewi, Suprayanti Martia; Sobir, Sobir; Syukur, M; Kisman, Kisman (AGROTEKSOS, 2023)
This study aimed to obtain information stability results 14 tomato genotypes grown in four lowland locations using multiple methods of parametric stability analysis. The experiments were conducted at four locations, namely Purwakarta, Lombok, Tajur and Leuwikopo. Experiments at each location using Randomized Complete Block Design (RCBD) with three replications which replicates nested within location. The method used were Francis and Kannenberg, Wrickle ekovalens, Finlay and Wilkinson, Eberhart and Russel, Wrickle ekovalens and AMMI . Research carried out shows based on the concept of static stability using the method of Francis and Kannenberg and Russell Eberhart, who declared stable genotype were IPBT3, IPBT53 and IPBT78. Based on the concept of dynamic stability using Wrikle ekovalens and Finlay & Wilkinson methods, stable genotype were IPBT3, IPBT8, IPBT33, IPBT34, IPBT57, IPBT60, IPBT64 and Intan. IPBT3, IPBT33, IPBT34, IPBT60 and Intan as stable genotypes under AMMI methods .